Respon Pertumbuhan Stek Durian (Durio zibethinus Murr.) terhadap Penambahan ZPT dan POC Kulit Pisang Kepok pada Fase Pembibitan - Nugraha, Faiz; Susiyanti, Susiyanti; Rumbiak, Julio Eiffelt; Sulistyorini, Endang (Fakultas Pertanian Universitas Udayana, 2024)
Growth Response of Durian (Durio zibethinus Murr.) Cuttings to the Addition of ZPT and POC Banana Kepok Peel in the Seeding Phase. The production of durian fruit in Indonesia fluctuates annually, yet there continues to be a high demand for durian. This research explores the use of Plant Growth Regulators (ZPT) and Liquid Organic Fertilizers (POC) to enhance durian propagation efficiency. The aim is to understand the effects of ZPT and POC on durian plant response, grafting models, and bud break time, aiming to produce high-quality durian seedlings. The experimental research method employed a Randomized Complete Block Design (RCBD) with cluster randomization. The study consisted of 2 factors with 3 replications each: ZPT Growtone (G1: 5 mg/l; G2: 10 mg/l; G3: 15 mg/l) and POC Banana Peel (P1: 100 ml/polybag; P2: 200 ml/polybag; P3: 300 ml/polybag), resulting in 27 experimental units. The results indicate that ZPT treatment influenced the percentage of successful grafting but did not affect bud break days, length of scion, leaf emergence, or rootstock length. Meanwhile, the POC banana peel treatment affected plant height and scion length but did not influence grafting success rate, bud break, leaf emergence, or rootstock length. There was no interaction observed between the effects of ZPT and POC banana peel on each parameter.